Gender mainstreaming: who wins?: gender and irrigated urban vegetable production in West Africa - Drechsel, Pay; Hope, Lesley; Cofie, Olufunke O. (2013)
Gender roles in agriculture can be quite specific, not only in view of particular labor inputs during the production cycle but also in terms of who farms and who trades certain crops. Using data collected over ten years in West Africa, this study looked at market-oriented urban vegetable production in West Africa and Ghana in particular. Gender disaggregated data on key issues such as access and control of resources, division of tasks, decision-making process and challenges faced was collected from farmers and traders. With several exceptions, a clear gender distinction emerged across the sub-region: men dominate urban vegetable farming, while women manage vegetable marketing. The general differentiation is attributed to societal norms, but other factors play a role as well. Female farmers, for example, feel constrained by existing irrigation practices that are energy-intensive and conflict with household duties. Male farmers, on the other hand, feel significantly oppressed by their dependency on credit and prices dictated by market women, and feel disadvantaged when entering the vegetable retail market. Improved irrigation technology could facilitate a better gender balance on the farm, but mainstreaming gender balance in vegetable wholesale and retail is likely to disadvantage women.